Protection of State symbols in trademarks under Article 6ter of the Paris Convention for the Protection of Industrial Property - Knodze, Krišjānis (Riga Graduate School of Law, 2023)
The thesis explores Article 6ter of the Paris Convention for the Protection of Industrial Property. It analyzes the requirements and limitations imposed on the registration of national symbols and their imitations as trademarks, focusing on the need to evaluate them differently from a heraldic point of view. The research highlights that visual comparisons alone are insufficient and emphasises the importance of comparing heraldic descriptions of symbols and visual representations of trademarks. The study also reveals the lack of a common understanding among member states regarding heraldic imitations. Additionally, it uncovers variations in the communication of symbols to the World Intellectual Property Organization (WIPO) and the absence of competent authorities in some states. Furthermore, the thesis examines the protection of State names, the interests of states in protecting intellectual property, and the reasons behind it. The findings also highlight the growing significance of national branding based on national identities.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Intellectual property law; Heraldic imitation; Paris Convention for the Protection of Industrial Property